Biocontrol potential of Antarctic endophytic bacteria - Iungin, Olga; Prekrasna-Kviatkovska, Yevheniia; Kalinichenko, Oleksandr; Savchuk, Yaroslav; Sidorenko, Marina; Mickevičius, Saulius (Ukrainian Antarctic Journal, 2024)
Antarctic endophytes, adapted to harsh environmental conditions, possess unique metabolic capabilities that can influence plant-microbe interactions. In this study, we investigated the impact of 15 plant growth-promoting bacterial strains isolated from Deschampsia antarctica and Colobanthus quitensis on the growth of phytopathogenic fungi. Besides everything else, among growth-promoting traits it was shown that bacteria synthesized biosurfactants, ammonia, and auxin-like hormones for plant growth, and also have shown significant growth in a wide temperature range. While these endophytes exhibited significant antifungal activity against agriculturally important fungi, we also observed the stimulation of fungal growth by certain strains. This dual role of endophytes highlights the complex and contextdependent nature of plant-microbe interactions. Our findings suggest that the effects of endophytes on plant health can be multifaceted. While they can directly inhibit pathogens, they can also indirectly influence the plant microbiome, potentially leading to beneficial and detrimental outcomes. Further research is needed to elucidate the mechanisms underlying these complex interactions and to harness Antarctic endophytes’ potential for sustainable agriculture.